Hardiness and problem-solving skills as preventive factors against smoking among adolescents - Abdollahi, Abbas; Abu Talib, Mansor (Canadian Center of Science and Education, 2014)
Smoking is the biggest threat to public health, and it remains a serious cause of death in the world; therefore, it is essential to develop our knowledge concerning the attitudes among adolescents toward cigarette smoking. This study was conducted to examine the associations among hardiness, problem-solving skills appraisal and attitude towards cigarette smoking in adolescents. The participants comprised of 550 high school students from Tehran, completed the self-report questionnaires. The structural equation modelling (SEM) estimated that adolescents with a high ability for hardiness, effective problem-solving confidence, internal personal control and approaching coping styles were more likely to report negative attitude towards cigarette smoking. The findings promote the value of problem-solving skills and hardiness as protective factors against smoking.